2012
DOI: 10.1161/strokeaha.112.671594
|View full text |Cite
|
Sign up to set email alerts
|

Final Infarct Volume Is a Stronger Predictor of Outcome Than Recanalization in Patients With Proximal Middle Cerebral Artery Occlusion Treated With Endovascular Therapy

Abstract: This study represents a retrospective analysis of a prospectively acquired database comprising 562 consecutive patients with acuteBackground and Purpose-The rationale for recanalization therapy in acute ischemic stroke is to preserve brain through penumbral salvage and thus improve clinical outcomes. We sought to determine the relationship between recanalization, clinical outcomes, and final infarct volumes in acute ischemic stroke patients presenting with middle cerebral artery occlusion who underwent endovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
139
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 184 publications
(154 citation statements)
references
References 28 publications
13
139
1
1
Order By: Relevance
“…21 Indeed, we and others have previously shown that leukoaraiosis severity is associated with a larger ischemic core, mismatch lost, and final infarct volume, supporting this hypothesis. 13,15,22 Indeed, subgroup analyses in patients with available follow-up imaging indicated that worse leukoaraiosis independently predicted larger infarct volumes.…”
Section: Multivariable Logistic Regression Analysis Of Factors Indepesupporting
confidence: 69%
“…21 Indeed, we and others have previously shown that leukoaraiosis severity is associated with a larger ischemic core, mismatch lost, and final infarct volume, supporting this hypothesis. 13,15,22 Indeed, subgroup analyses in patients with available follow-up imaging indicated that worse leukoaraiosis independently predicted larger infarct volumes.…”
Section: Multivariable Logistic Regression Analysis Of Factors Indepesupporting
confidence: 69%
“…Previous studies have examined the association between post-treatment infarct volume (measured at 24-48 hours) and functional ability at 90 days as measured by the mRS. 8,9 Our results show that post-treatment infarct volume is a strong independent predictor of 90-day mRS. The mRS at 90 days is best predicted when information on acute treatment response (change in NIHSS from baseline to 24 hours) is available along with post-treatment infarct volumes.…”
Section: Discussionmentioning
confidence: 59%
“…Time to randomization was not a significant predictor of post-treatment infarct volume in our analysis, but we hypothesize that this is because of study design; imaging selection used in the ESCAPE trial (subjects selected using favorable imaging criteria independent of time from onset to randomization) may have contributed to these results. Stroke onset time is also imprecisely measured with many subjects either waking up after stroke onset or only last seen normal at a certain time.Previous studies have examined the association between post-treatment infarct volume (measured at 24-48 hours) and functional ability at 90 days as measured by the mRS. 8,9 Our results show that post-treatment infarct volume is a strong independent predictor of 90-day mRS. The mRS at 90 days is best predicted when information on acute treatment response (change in NIHSS from baseline to 24 hours) is available along with post-treatment infarct volumes.…”
mentioning
confidence: 59%
See 2 more Smart Citations